2023
DOI: 10.1002/chem.202303120
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Organic Ferroelectric Materials from Donor–Acceptor Systems

Shubhankar Barman,
Aritri Pal,
Anurag Mukherjee
et al.

Abstract: Amongst different class of organic systems, donor(D)‐acceptor(A) charge‐transfer (CT)‐ complexes were recognized promising for ferroelectricity owing to their neutral‐to‐ionic phase transition at low temperature. This review presents an overview of different supramolecular D‐A systems, explored for ferroelectric (FE) phase transitions. Discussion begins with a general introduction of ferroelectricity and different associated parameters. Then it moves on to show early examples of CT‐cocrystals that showed FE pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
0
0
0
Order By: Relevance
“…8,11 In this context, molecular design has become a powerful tool to tune (complex) energy landscapes in self-assembly, as evident by detailed analysis of a wide range of molecular building blocks. 12–38 While various studies have revealed that the intermolecular interactions encoded in the monomer design largely govern the self-assembly outcome, predicting these interactions by molecular design is far from easy. For example, we recently found that the functionalization of dye molecules with bulky substituents may unexpectedly stabilize H-type face-to-face stacking interactions despite the significant steric hindrance, contrary to conventional expectations based on literature.…”
Section: Introductionmentioning
confidence: 99%
“…8,11 In this context, molecular design has become a powerful tool to tune (complex) energy landscapes in self-assembly, as evident by detailed analysis of a wide range of molecular building blocks. 12–38 While various studies have revealed that the intermolecular interactions encoded in the monomer design largely govern the self-assembly outcome, predicting these interactions by molecular design is far from easy. For example, we recently found that the functionalization of dye molecules with bulky substituents may unexpectedly stabilize H-type face-to-face stacking interactions despite the significant steric hindrance, contrary to conventional expectations based on literature.…”
Section: Introductionmentioning
confidence: 99%